Literature Review: Implementation of Differentiated Learning Strategies in Supporting Student Learning Outcomes - Sodikin; Tania Avianda G; Mutiara Dwi C; Ubaidillah, Andre Prasetyo (Education, Science, and Technology International Conference, 2025)
This study aims to analyze the implementation of differentiated learning strategies in supporting student learning outcomes. Differentiated learning adjusts teaching methods and materials based on individual learning needs and styles, which is important in the context of 21st century education. Through a literature study covering national and international articles in the last ten years, this study found that the implementation of this strategy can improve student learning activities and outcomes at various levels of education, including junior high and senior high schools. The results showed that students involved in differentiated learning showed significant improvements in critical thinking and problem-solving skills. Thus, differentiated learning has proven effective in meeting students’ diverse learning needs and making a positive contribution to their academic outcomes. This study recommends that teachers continue to implement and develop differentiated learning strategies to achieve optimal learning outcomes.